Mutation in Fbxo11 Leads to Altered Immune Cell Content in Jeff Mouse Model of Otitis Media - Vikhe, Pratik P.; Tateossian, Hilda; Bharj, Gurpreet; Brown, Steve D.M.; Hood, Derek W. (Frontiers in Genetics, 2020)
The Jeff mouse mutant carries a mutation in the F-box only 11 gene (Fbxo11) and heterozygous animals display conductive deafness due to the development of Otitis Media (OM). The Fbxo11 locus is also associated with chronic otitis media with effusion (COME) and recurrent OM in humans. The Jeff mutation affects the ability of FBXO11 to stabilize p53 that leads to perturbation in the TGF-beta/Smad2 signalling pathway important in immunity and inflammation. In the current study, we evaluated the effect of the Jeff mutation on the immune cell content using multicolour flow cytometry. In blood of Jeff heterozygotes, we observed a significant increase in the number of NK, dendritic (CD11b+), neutrophils and NKT cells and a significant decrease in effector T-helper and B-lymphocytes compared to wild-type controls. The percentage of NK cells significantly decreased in the lungs of Jeff heterozygotes, with a concomitant reduction in B-lymphocytes and T-cytotoxic cells. In the spleen, Jeff heterozygotes displayed a significant decrease in mature B-lymphocytes, effector T-helper and naïve T-cytotoxic cells. Neutrophils, dendritic and NKT cells dominated bulla fluid in Jeff heterozygote mice. Similar analysis carried out on Fbxo11tm2b/+ heterozygotes, which carry a null allele, showed no difference when compared to wild-type. Cytokine/chemokine analysis revealed a significant increase in the G-CSF, GM-CSF, sTNFRI, TPO and IL-7 levels in Jeff heterozygote serum compared to wild-type. This analysis increases our understanding of the role played by Fbxo11, a gene associated with human OM, in the systemic and localized cellular immune response associated with increased susceptibility to OM.